Develop Bactra system to determine Mutagens in the Environment, Food Second: use Hashr agents acridine orange - Baghdad Science Journal (مجلة بغداد للعلوم)
Use Almtafr Alcderan orange, one of the factors Hashr Alttafaria to study Alatjabh isolates elected on the basis of specifications so that was a positive response with mutagen record and system consisting of three isolates used Alcderan orange graded concentrations and under specific Trov similar conditions Alttafar Pal NTG compared